Kuat Tekan Beton Geopolymer Optimum Pada Variasi Perbandingan Bahan Penyusun (20:80 S/D 40:60) Dan Pada Variasi Waktu Pencampuran (5 S/D 15 Menit) - Septia Ningrum, Rina; , Ir. Suhendro Trinugroho, M.T; , Ir. Aliem Sudjatmiko, M.T (2016)
Concrete is a building material that is composed of the main composition of coarse aggregate, fine aggregate, water, and Portland Cement. Concrete lately more often gets criticism, because of greenhouse gas emissions (carbon dioxide) generated in the cement production process. With these considerations, the development of new concrete binder called geopolymer concrete. One of the materials used in the manufacture of geopolymer concrete is coal fly ash (fly ash). By making use of fly ash as a substitute ingredient of cement is considered to safeguard the environment and reduce the cost of construction. In this study, the test object used is cylindrical, with a diameter of 15 cm and 30 cm high. Tests carried out at the time of compressive strength of concrete was only 28 days. Variations in concrete testing include: (1) Test the strength of concrete on the variability of the material making up 20%: 80% and the variety of mixing time of 5 s / d 15 minutes (2) Test the strength of concrete on the variability of the material making up 25%: 75% and the variety of mixing time of 5 s / d 15 minutes (3) Test the strength of concrete on the variability of the material making up 30%: 70% and the variety of mixing time of 5 s / d 15 minutes (4) Test the strength of concrete on a variation of the building blocks 35 %: 75% and thevariety of mixing time 5 s / d 15 minutes (5) Test the strength of concrete in the variation of constituents of 40%: 60% and the variety of mixing time 5 s / d 15 minutes. From the tests it can be concluded that the mixing time of the most optimum concrete mix was 7.5 minutes. If less than 7.5 minutes resulting binder less than the maximum holding capacity. And if the mixing time of more than 7.5 minutes resulting in a decreased adhesion binder. As for the subject to variations in concrete to total use of fly ash, it can be concluded that the higher the content of fly ash there is a tendency compressive strength is low, it's likely due to the influence of moisture content used in the mixture is obtained based on a count of the weight of fly ash used in each variation. So when the weight of the fly ash is higher, then the need for water is also getting higher and result in overly dilute the fresh concrete, so concrete compressive strength decreases.